Disseminated pneumocystis carinii infection in AIDS. Issue 10 (October 1991) - Coker, R J; Clark, D; Claydon, E L; Gompels, M; Ainsworth, J G; Lucas, S B; Miller, R; Goldin, R D; Pinching, A J; Harris, J R
Abstract : Eight patients with AIDS and Pneumocystis carinii infection were studied. Protean manifestations were a feature not untypical of disseminated pneumocystosis. Aerosolised pentamidine as prophylaxis against P carinii pneumonia was ineffective at suppressing dissemination. The knowledge that extrapulmonary infection can occur has implications for the detection and treatment of, and prophylaxis against, P carinii infection. The survival of patients with disseminated pneumocystosis is particularly poor, and may be due to a lack of clinical awareness and consequent delay in diagnosis.